IMPLEMENTATION OF SCRAPBOOK MEDIA LEARNING ON THE ABILITY TO WRITE REVIEW TEXTS IN GRADE VIII - Harlen Simanjuntak; Tumpal Richardo Sirait; Sahat Taruli Siahaan (STKIP Pesisir Selatan, 2026)
Implementation of Scrapbook Media Learning on the Ability to Write Review Texts of Class VIII Students of SMP Negeri 12 Medan Academic Year 2025/2026. This research is a quantitative experimental research with a two-group pretest and posttest research design. The population is 186 class VIII students, and the research sample is 31 class VIII-A students and 31 class VIII-B students determined by cluster random sampling technique.Data analysis techniques included normality tests with F tests, homogeneity tests, and hypothesis tests. After conducting research on the pretest and posttest regarding the use of scrapbook media, the average pretest score was 47.9 with deviation standard 17.07, And average mark posttest as big as 76.2 with standard deviation 17.77.Based on results test hypothesis in study This, done test t on level of significance???? = 0.05 and the result of t count is > ttable (4.1 > 2.041). Thus, H₀ is rejected and Hₐ accepted. Results test prerequisite data pretest And posttest show that the sample is normally distributed and homogeneous.It can be concluded that there is an influence of the implementation of learning using scrapbook media on students' abilities. write text review student class VIII JUNIOR HIGH SCHOOL Country 12 Medan year 2025/2026 academic year.